The Youth Soccer Coaches' Visions and Thoughts of Leader Support - Hertting Krister; Kostenius Catrine (Sciendo, 2016)
The Objectives: The European Commission has highlighted the use of sports as an important venue for engaging citizens in health-enhancing activities, physical activity, volunteerism and active citizenship. Coaching is a central component of sports for children and youth, but there is little research on the promotion of sports coaches' health. In the light of this gap, the aim of this paper was to elucidate youth soccer coaches' visions and thoughts regarding leadership support from clubs and soccer associations.